Modelling and optimisation of oil palm biomass value chains and the environment–food–energy–water nexus in peninsular Malaysia - Rubinsin, Nowilin James; Wan Daud, Wan Ramli; Kamarudin, Siti Kartom; Masdar, Mohd Shahbudin; Rosli, Masli Irwan; Samsatli, Sheila; Tapia, John Frederick D.; Wan Ab Karim Ghani, Wan Azlina; Hasan, Azhan; Lim, Kean Long (Elsevier, 2021)
This study aims to develop a decision model to optimise the oil palm biomass value chains by minimising the environmental impact whiles generating economy value from their bioproducts. The model considers two major components, namely, a fuzzy analytic hierarchy (FAHP) framework and a multi-objective optimisation model. Both components will be used by integrating the priorities of the environmental and economic impacts obtained from experts' judgement with the multi-objective optimisation model to generate an optimal solution based on expert's judgement. The framework used to study different case study for the oil palm industry in Peninsular Malaysia. Results show that a maximum profit of 267,116,398 USD per year can be achieved. However, to minimise the environmental impact, a 34% cut of the profit is needed to reduce 91% of CO2 emissions generated and 97% of water consumption. Moreover, the model generates optimal pathways by selecting the processing facilities that are needed in the value chain to achieve the objectives. The biomass or bio-product distribution networks around Peninsular Malaysia are also presented in this paper. Several scenarios are discussed to observe the effects on the optimal value chain solutions by manipulating the production level. On the basis of the results, the interactions of the environment–food–energy–water nexus are investigated. Therefore, this study can contribute to the improvement of oil palm industry policies while addressing sustainability issues through the proposed value chain model.